Effect of fuel tax on carbon dioxide emissions in Sweden - Vinberg, Hanna (2020)
Greenhouse gases are increasingly causing both global climate changes and local health issues. In particular, carbon dioxide emissions represent 81% of total greenhouse gas emissions. There is evidence that fuel taxes can be adopted as a mitigation measure to lower greenhouse gas emissions and contribute to climate change adaptation goals. Using a panel data approach, this study examined the impact of Swedish fuel taxes on carbon dioxide emissions in various municipalities. The empirical model involved a set of explanatory variables, identified based on the relevant literature that are believed to influence the dependent variable (carbon dioxide emissions), namely: fuel taxes (the variable of interest), the number of passenger cars and the population density in a municipality in a given year. Moreover, to capture the spatial effects, the study included the regional classification of each municipality (rural or urban) as an explanatory variable. Overall, the results indicated that fuel tax has a statistically significant negative effect on carbon dioxide emissions. Specifically, a 1% increase in fuel tax in a given municipality would be associated with a reduction of 0.8% in the amount of carbon dioxide emissions. Distinguishably, the results revealed a positive and statistically significant relationship between carbon dioxide emissions and the municipalities being classified as urban. In light of these results, the study concludes that fuel tax could be utilized as a climate policy instrument, but it should be complemented by other socio-economic and environmental policies tailored to each municipality to achieve the intended effect.